The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.07.31.230243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 suppresses mRNA expression of selenoproteins associated with ferroptosis, endoplasmic reticulum stress and DNA synthesis

Abstract: A significant, positive association between selenium status and COVID-19 prognosis has recently been identified. The present study investigated the influence of SARS-CoV-2 on host selenoproteins which mediate many beneficial actions of selenium. We found that SARS-CoV-2 suppressed mRNA expression of selenoproteins associated with ferroptosis (GPX4), ER stress (SELENOF, SELENOK, SELENOM and SELENOS) and DNA synthesis (TXNRD3) in Vero cells, providing a deeper insight into the connection between selenium and SAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Recently, a ferroptosis signature was reported in a case report of COVID-19 patient (48-year-old, male), showing 4-HNE, a reactive breakdown product of the lipid peroxides or oxidized phosphatidylcholine was positive in myocardial tissue staining and in the proximal tubules of acute kidney injury, with decreased lymphocytes in the blood 63 . An in vitro study also showed SARS-CoV-2 suppressed GPX4, the brake of ferroptosis 43 . These studies demonstrated the involvement of ferroptosis in SARS-CoV-2 infection and its potential contribution to the multiple organ damage.…”
Section: A Hypothesis On the Association Between Covid-19 And Ferroptmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, a ferroptosis signature was reported in a case report of COVID-19 patient (48-year-old, male), showing 4-HNE, a reactive breakdown product of the lipid peroxides or oxidized phosphatidylcholine was positive in myocardial tissue staining and in the proximal tubules of acute kidney injury, with decreased lymphocytes in the blood 63 . An in vitro study also showed SARS-CoV-2 suppressed GPX4, the brake of ferroptosis 43 . These studies demonstrated the involvement of ferroptosis in SARS-CoV-2 infection and its potential contribution to the multiple organ damage.…”
Section: A Hypothesis On the Association Between Covid-19 And Ferroptmentioning
confidence: 92%
“…Iron is considered a critical player in COVID-19 pathogenesis 42 . A basic study used patient-derived SARS-CoV2 (SZ005) to infect African green monkey kidney (Vero) cells and found the expression of GPX4 was significantly decreased in mRNA levels, suggesting the association between SARS-CoV-2 and ferroptosis 43 . Owing to the lack of GPX4, GSH cannot be peroxidated to reduce lipid ROS generated from Fenton reaction.…”
Section: A Hypothesis On the Association Between Covid-19 And Ferroptmentioning
confidence: 99%
“…[5,6,7,8] SARS-CoV-2, like other RNA viruses, sequesters selenium causing selenium levels to drop during infection. [6,9] SARS-CoV-2 may infect cells in bone marrow, supressing red blood cell formation. [10] Selenium status is inversely associated with haemolysis in SCD, and may both inhibit haemolysis and enhance erythropoiesis in SCD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, selenium was observed to suppress the release of the inflammatory precursor cytokine that is activated by pathogens 12,13 . In cell studies, it was observed that cells infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) decreased selenoprotein synthesis and this decrease was found to be associated with the increase of IL‐6, an inflammatory marker 14 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 In cell studies, it was observed that cells infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) decreased selenoprotein synthesis and this decrease was found to be associated with the increase of IL-6, an inflammatory marker. 14 On the other hand, it was mentioned that selenium supplementation was beneficial for the regulation of immune response against thyroid autoimmunity during pregnancy and the post-partum period. 15 In an animal study, maternal selenium deficiency during pregnancy caused reduced fetal growth by reduced fetal glucose concentrations.…”
Section: Introductionmentioning
confidence: 99%